The impact of a Fuel mixture On Matic Motorbike Performance - Marfizal; Fadli Nur Permadi (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) - ITP, 2021)
The research conducted in this paper is related to testing the performance of a 4-stroke engine using Pertamax, Pertalite and Pertalite 50% Pertamax 50% fuel. The test was carried out by varying the power from 5000 to 8000 rpm. The performance that will be compared from the three types of fuel is acceleration, speed, power and torque. Tests were carried out using Super Dyno 50L. The results of this test are used to compare the performance of the three types of fuel. In this study, it was found that the use of Pertamax on the Pertamax 4 stroke engine had performance in Pertalite and a mixture of Pertamax usage 50% Pertalite 50%. Judging from its performance for Pertamax, the acceleration value is 0.26% to 0.01%, the speed ranges from 0.54% to 45%, the higher power is 1.82% to 24.04 %, greater torque 6.65% to 25.67%. In general, it can be concluded that Pertamax has a better performance then followed by a mixture of Pertalite 50% Pertamax 50%.